Extraction and Characterization of Antibacterial Compound from Aspergillus niger - Al-Shaibani, Abdulwahid B A; Al-Shakarchi, Faiz I; Ameen, Rasha S (Al-Nahrain Journal of Science, 2013)
To investigate the antagonistic properties of the fungal isolates (Aspergillus niger, Penicillium sp, Alternaria sp) obtained from inflamed patients eyes against pathogenic bacteria(Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus epidermidis, Bacillus sp) isolated from keratitic patient, agar well method was used, in which the antibacterial activity of fungal isolates was examined by testing the effect of their culture filtrates on growth of the bacterial pathogens. For this purpose (52) corneal scraping samples were taken from patients of microbial keratitis referred to Ibn Al-Haetham Eye Teaching Hospital in Baghdad. Results showed that 6 (21.42%) were positive for fungal occurrence after culturing on the related selective media, the fungal isolates were belonged to A. niger 3 (10.71%), Penicillium sp 2 (7.14%), Alternaria sp 1 (3.57%). Results revealed that A.niger possessed the highest inhibitory effect against P.aeruginosa, S.aureus, S.epidermidis, Bacillus sp with inhibition zones of (15, 25, 30, 32) mm in diameter, respectively, followed by Penicillium sp. Adversely, while no inhibitory effect was recorded by the filtrate of Alternaria sp used. Among on bacteria Bacillus sp was the most effective and sensitive isolate.The suspected antibacterial compound produced by A.niger was characterized and partially purified by using infrared (IR), UV absorbance and thin layer chromatography (TLC). Results show that the compound appeared as a single dark spot on the TLC plate under UV light that had Rf value of 0.45. From IR and UV analysis it was confirmed that the compound was aromatic- nitrogenous in nature. From such achievement, it can be said that the active antibacterial compound might be tensidol which is an alkaloid or a new derivative of alkaloid.